Database analysis of oral atropine treatment of infantile hypertrophic pyloric stenosis. A ten-year single-center experience - Vujović, Dragana; Lukač, Marija; Sretenović, Aleksandar; Pejanović, Jelena; Jovanović, Branislav; Pavićević, Polina; Krstajić, Tamara; Trajković, Goran; Pavlović, Vedrana; Topličić, Djordje; Sindjić-Antunović, Sanja (Vojnosanitetski pregled, 2021)
Background/Aim. Infantile hypertrophic pyloric stenosis (IHPS) is the most common cause of surgery in newborns and young infants. Conservative treatment of IHPS is of great importance because it spares the newborn from stress caused by surgery and general anesthesia. The aim of this study was to evaluate the impact of various oral administration regimens of atropine on its efficacy in treating IHPS. Methods. The study included 45 patients with IHPS, conservatively treated by atropine sulfate in the period from 2006 to 2016. Clinical examination, laboratory analysis, and ultrasonography were performed on all patients on admission. The efficacy of treatment with different oral dosage regimens was analyzed and potential predictive factors of the negative outcome were defined. The evaluation of the success of the treatment was statistically analyzed by the method of the multivariate logistic regression model. Results. Out of 45 patients, 36 (80%) were successfully cured (p = 0.0008, without the need for surgery and without any complications. Gender prevalence, age, birth weight, body weight on admission, duration of symptoms, pyloric muscle thickness, and length had no statistically significant individual effect on the success of the atropine treatment. Patients who received a progressively increased dose of atropine had an 18 times higher risk of surgery, patients with hypochloremic alkalosis (HCA) had a 15 times higher risk, while others, with more than 5 vomitings within the first three days of the therapy, were 9 times more likely to be surgically treated. Conclusion. High success rate and no side effects represent an orally administered atropine treatment as a valid alternative choice for non-operative management of IHPS. Administration of initially high doses was shown to be more effective in relation to gradually increased oral doses of atropine sulfate. HCA and continued vomiting are considered as potential predictive factors of negative outcomes of the atropine treatment.